Prader-Willi syndrome: an update on obesity and endocrine problems - Su Jin Kim; Sung Yoon Cho; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2021)
Prader-Willi syndrome (PWS) is a rare complex genetic disorder that results from a lack of expression of the paternally inherited chromosome 15q11-q13. PWS is characterized by hypotonia and feeding difficulty in early infancy and development of morbid obesity aggravated by uncontrolled hyperphagia after childhood and adolescent. Dysmorphic facial features, delayed motor and language development, various degrees of cognitive impairment, and behavioral problems are common in PWS. Without early, intensive nutritional therapy along with behavioral modification, PWS patients develop severe obesity associated with type 2 diabetes, obstructive sleep apnea, right-side heart failure, and other obesity-related metabolic complications. Hypothalamic dysfunction in PWS can lead to several endocrine disorders, including short stature with growth hormone deficiency, hypothyroidism, central adrenal insufficiency, and hypogonadism. In this review, we discuss the natural history of PWS and the mechanisms of hyperphagia and obesity. We also provide an update on obesity treatments and recommendations for screening and monitoring of various endocrine problems that can occur in PWS.